Diagnostic and therapeutic process of neurofibromatosis type 1 and type 2 - Leśniewski, Michał; Welian-Polus, Iwona; Oleksak, Izabela; Maliszewska, Karolina (Journal of Education, Health and Sport, 2024)
Neurofibromatosis is one of the most common genetic diseases. It is inherited in an autosomal dominant manner. It is divided into two genetically distinct subtypes, characterised by multiple skin lesions and tumours of the peripheral and central nervous system. Neurofibromatosis type 1, or Recklinghausen’s disease, is the most common phakomatosis. The disease is genetically determined by a mutation of the neurofibromin- 1 gene on chromosome 17. Neurofibromatosis type 2 accounts for 3% of all cases. The disease is genetically determined - caused by a mutation of the neurofibromin-2 gene on chromosome 22. The diagnostic and therapeutic process of neurofibromatosis is a major challenge for clinicians. Given the complexity of the problem, we have reviewed the literature on the diagnostic and therapeutic possibilities of the disease.